1999
DOI: 10.1029/1999jd900055
|View full text |Cite
|
Sign up to set email alerts
|

Improving first‐order snow‐related deficiencies in a regional climate model

Abstract: Abstract. A climate version of the Regional Atmospheric Modeling System (RAMS) is used to simulate snow-related land-atmosphere interactions in the Great Plains and Rocky Mountain regions of the United States. The availability of observed snow-distribution products allow snow-water-equivalent distribution data to be assimilated directly into the RAMS simulations. By performing two kinds of model integrations, one with and one without assimilating the snow-distribution observations, the differences between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 25 publications
1
52
0
1
Order By: Relevance
“…Some studies proposed a correction term allowing for the precipitation to increase linearly with height in the form: 1 P vint = P obs (1 − β z) when z i is higher than z obs , and equal to 0 when z i is lower that z obs (e.g., Liston et al, 1999). In this correction term, β is a station-dependent parameter whose value has to be determined with care.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies proposed a correction term allowing for the precipitation to increase linearly with height in the form: 1 P vint = P obs (1 − β z) when z i is higher than z obs , and equal to 0 when z i is lower that z obs (e.g., Liston et al, 1999). In this correction term, β is a station-dependent parameter whose value has to be determined with care.…”
Section: Resultsmentioning
confidence: 99%
“…We assume that the smoothing out of smallscale snow depth heterogeneities originating from processes such as snowdrift or avalanches reveals the large-scale topographic influences on precipitation and the shortwave radiation balance. Our hypothesis is motivated by the observation of Liston et al (1999), in that, in contrast to summer convective-precipitation systems, the spatial distribution of winter precipitation is more influenced by topographic distributions. Furthermore, it is motivated by the results of Grünewald et al (2013) and Melvold and Skaugen (2013), which confirmed that the snow depth distribution is dominated by topography at scales of several hundred meters.…”
Section: Introductionmentioning
confidence: 99%
“…Frequently, they lack a subgrid snow distribution representation which is a shortcoming that deteriorates atmospheric interaction simulations (cf. Liston et al, 1999). In general, the purpose of subgrid parameterizations is to account for subgrid scale processes, i.e., unresolved processes, with analytical approximations in largescale model systems.…”
Section: Introductionmentioning
confidence: 99%
“…Such deterministic high-resolution modeling facilitates a better comparison and validation with ground observations but is restricted to small model domains for computational reasons. However, SnowModel also includes the ability to sim- ulate snow distributions over large areas (e.g., the ice-free parts of Greenland, several 100 000 km 2 ) using, for example, subgrid snow distribution representations (e.g., Liston et al, 1999;Liston, 2004;Liston and Hiemstra, 2011). Gisnås et al (2014) recently presented a statistical approach to account for the impact of the small-scale variability of snow depths on ground temperatures that is applicable on large spatial domains.…”
Section: Scaling Strategies From Gcm To Plot Scalementioning
confidence: 99%